Comprehensive assessment of phenolic compounds and antioxidant performance in the developmental process of jujube (Ziziphus jujuba Mill.). (September 2017) - Xie, Pu-jun; You, Feng; Huang, Li-xin; Zhang, Cai-hong
Graphical abstract: Highlights: Jujube peel performs better than its pulp on phenolic profiles and antioxidation. Jujube peel in stage 2 indicates more phenolics and powerful antioxidation. Peel color, phenolics and antioxidantion are connected in the developmental process. Phenolic content in the peel shows a positive relevance to its antioxidation. Abstract: To reveal the relationship between peel color variation, phenolic content and antioxidant performance during the developmental process of seven Chinese jujubes, the content variation of specific phenolic compounds of these jujube peel extracts were determined. Simultaneously, their jujube peel color values and antioxidant performances were measured by CIE L ∗ a ∗ b ∗ and, DPPH and the ABTS + scavenging capacity, respectively. The contents of total phenolics and flavonoids, including gallic acid, chlorogenic acid, caffeic acid, coumarin, (+)-catechin, p -coumaric acid, ferulic acid, quercetin, (−)-epicatechin and rutin as well as the DPPH scavenging capacity dramatically increased as the peel color became darker from stage 1 to stage 2, but decreased in stage 3. Interestingly, the ABTS + scavenging capacity of the peel extract declined continuously due to a different action mechanism. All these suggest that the jujube peel color variation can indicate polyphenol content and antioxidant properties in the development period.